Nuclear Quadrupole Resonance: A Technique to Control Hydration Processes in the Pharmaceutical Industry - Limandri, Silvina Paola (2011)
Pharmaceuticals can exist in many solid forms, which can have different physical and chemical properties. These solid forms include polymorphs, solvates, amorphous, and hydrates. Particularly, hydration process can be quite common since pharmaceutical solids can be in contact with water during manufacturing process and can also be exposed to water during storage. In the present work, it is proved that NQR technique is capable of detecting different hydrated forms not only in the pure raw material but also in the final product (tablets), being in this way a useful technique for quality control. This technique was also used to study the dehydration process from pentahydrate to trihydrate.